Clinical outcomes in the surgical treatment of pyoinflammatory diseases of pelvic organs: the possibility of predication - Maricheda, V.; Rozhkovskaya, N.; Sitnik, P. (Journal of Education, Health and Sport, 2018)
Among inflammatory processes of female genital more than 80% account for the pathology of uterine appendages and the share of complicated forms of purulent inflammatory diseases accounts 4 - 10%. Diagnosis and prediction of PID are based on clinical, laboratory, biochemical, immunological parameters and data of instrumental research methods which are often cumbersome and not always available in most surgical hospitals. The objective: to identify significant predictors of clinical outcomes in the surgical treatment of pyoinflammatory diseases of the pelvic organs. 108 women of fertile age with PID were examined. 73 of them were treated conservatively (group I, comparison). Group II (main) consisted of 35 women who underwent surgery according to vital indications. Results. The main group patients were operated on with laparotomy access, adnexectomies (right-sided - 27.8%, left-sided - 22.2%) constituted a considerable number. In 22.2% of cases, total hysterectomy was performed, and the same number of patients abdominal cavities were drained in the postoperative period. A telephone survey conducted showed that the overall response rate decreased in proportion to the time elapsed since discharge from the hospital, e.g. in three years only 13.2% of the former patients had been in contact. Conclusion.The highest predictive value in the operative treatment of pyoinflammatory diseases of the pelvic organs has TNF and procalcitonin (PPV = 0.77 and 0.81, respectively).